Scientific justification of using of oat malt flour and gumarabic «FIBREGUM» in butter biscuit technology - Skrypko, Anhelina; Obolkina, Vera; Kyianytsia, Svetlana (My University, 2013)
The consumer properties of pastry items depend on the quality of recipe components, their chemical composition and technological properties. The sprouted grains contain the entire set of ingredients necessary for a balanced diet: low molecular weight proteins, amino acids, carbohydrates, food fibers, minerals, vitamins.
Keywords: biscuit; flour; dough structural- mechanical; печиво; борошно; структурно-механічні властивості тіста; кафедра технології хлібопекарських і кондитерських виробів